Behaviour of Soft Clay Foundation Beneath an Embankment - Kim Huat, Bujang (Universiti Putra Malaysia Press, 1994)
As a material, soft clay poses many challenges to geotechnical engineers. The material responds in a spectacular manner to stress changes. The paper describes the behaviour of five embankments constructed on lightly over consolidated soft Malaysian marine clays. The main finding is that the clay response to construction is not truly undrained. Significant consolidation develops initially in the over consolidated clay, which becomes normally consolidated during construction. Undrained behaviour develops only in the normally consolidated clay during the initial stages of construction.